Reticulocyte Indices in Diagnosis and Control of Effectiveness of Treatment of Iron Deficiency Conditions in Children - I. N. Zakharova; I. S. Tarasova; V. M. Chernov; E. B. Machneva; T. M. Vasilyeva (Union of pediatricians of Russia, 2016)
High prevalence of iron-deficiency conditions (IDC) in children dictates the need in searching for sensitive, accurate and simple methods of identifying such diseases on early stages of development. New methods of laboratory screening diagnosis are especially needed. The article presents an analysis of new methods of IDC laboratory diagnosis - hematological and biochemical. It presents a discussion of role of a new parameter - mean reticulocyte hemoglobin content (CHr) - for IDC diagnosis and treatment effectiveness control. The article presents data on CHr sensitivity and specificity as compared with the other hematological parameters frequently used for IDC diagnosis.